Factor VIII antibody immune complexes modulate the humoral response to factor VIII in an epitope-dependent manner - Batsuli, Glaivy; Ito, Jasmine; York, Elizabeth S.; Cox, Courtney; Baldwin, Wallace; Gill, Surinder; Lollar, Pete; Meeks, Shannon L. (Frontiers in Immunology, 2023)
Introduction: Soluble antigens complexed with IgG antibodies can induce robust adaptive immune responses in vitro and in animal models of disease. Factor VIII immune complexes (FVIII-IC) have been detected in individuals with hemophilia A and severe von Willebrand disease following FVIII infusions. Yet, it is unclear if and how FVIII-IC affect antibody development over time. Methods: In this study, we analyzed internalization of FVIII complexed with epitope-mapped FVIII-specific IgG monoclonal antibodies (MAbs) by murine bone marrow-derived dendritic cells (BMDC) in vitro and antibody development in hemophilia A (FVIII -/-) mice injected with FVIII-IC over time. Results: FVIII complexed with 2-116 (A1 domain MAb), 2-113 (A3 domain MAb), and I55 (C2 domain MAb) significantly increased FVIII uptake by BMDC, but only FVIII/2-116 enhanced antibody titers in FVIII -/-mice compared to FVIII alone. FVIII/4A4 (A2 domain MAb) showed similar FVIII uptake by BMDC to isolated FVIII, yet significantly increased antibody titers when injected in FVIII -/-mice. Enhanced antibody responses observed with FVIII/2-116 and FVIII/4A4 complexes in vivo were abrogated in the absence of the FVIII carrier protein von Willebrand factor.Conclusions: These findings suggest that a subset of FVIII-IC modulate the humoral response to FVIII in an epitope-dependent manner, which may provide insight into the antibody response observed in some patients with hemophilia A.